EFEK PEMBERIAN PROBIOTIK PADA PENDERITA SINDROM METABOLIK; STUDI LITERATUR - Desi Aliefia; Abdullah, Dessy; Tri Puspita Prihatinningrum AF; Zukhri Zainun (Nusantara Hasana Journal, 2024)
Developments in probiotic therapy have shown potential to help improve gastrointestinal health. Several studies have been conducted to test the benefits of probiotic use, both in the context of prevention and treatment of various diseases. This article reviews various research results related to the potential use of probiotics in metabolic syndrome. The literature discussing the mechanism of action of probiotics and clinical evidence for their use in conditions such as diabetes, dyslipidemia, and non-alcoholic liver disease are comprehensively reviewed. Although further research is needed, the management of gut microbiota through probiotic administration shows promising prospects as a complementary strategy in the management of metabolic syndrome. The imbalance of gut microbiota, known as dysbiosis, can contribute to the development of various metabolic diseases (Patel, R. and DuPont, L, H., 2015). Recent studies have shown that probiotic administration can improve the composition and function of gut microbiota, thereby helping to prevent or improve symptoms of various diseases associated with metabolic syndrome (Shi, Q. et al., 2022). One of the main mechanisms of probiotics is through their ability to maintain the balance of gut microbiota. By suppressing the growth of pathogenic bacteria and improving the composition of the gut microbiota, probiotics can help overcome problems associated with dysbiosis.